A group-based HIV and sexually transmitted infections prevention intervention for lesbian, bisexual, queer and other women who have sex with women in Calgary and Toronto, Canada: study protocol for a non-randomised cohort pilot study. Issue 4 (23rd April 2014) - Logie, Carmen H; Navia, Daniela; Rwigema, Marie-Jolie; Tharao, Wangari; Este, David; Loutfy, Mona R
Abstract : Introduction: The limited research that exists suggests that lesbian, bisexual queer (LBQ) and other women who have sex with women are at similar risk for sexually transmitted infections (STI) as heterosexual women. However, scant research has evaluated HIV and STI prevention strategies for LBQ women. The authors present the rationale and study protocol for developing and pilot testing a psychoeducational group-based HIV and STI prevention intervention with LBQ women in Calgary and Toronto, Canada. Methods and analysis: This is a multicentre non-randomised cohort pilot study. The target population is LBQ women in Calgary and Toronto, Canada. The authors aim to recruit 40 participants using purposive peer-driven recruitment methods. Participants will conduct a pretest followed by a 2-day group programme of six 2 h sessions addressing stigma, STI and HIV prevention, healthy relationships, safer sex self-efficacy, self-worth, social support and LBQ community engagement. Participants will conduct a post-test directly following the intervention and 6 weeks after the intervention. The primary outcome is safer sex practices; our prespecified index of clinically significant change is an effect size of 0.50. Secondary outcomes include: safer sex self-efficacy, STI testing frequency, STI knowledge, resilient coping, social support, sexual stigma, access to care, depression and self-esteem. We will conduct mixed-effects regression to calculate mean outcome pre–post test score change. Ethics and dissemination: Research ethics approval was attained from the Office of Research Ethics (REB: 29291), University of Toronto, Toronto, Ontario, Canada. Trial results will be published according to the Transparent Reporting of Evaluations with Non-randomised Designs (TREND) statement, regardless of the outcomes. Trial registration number: This study is registered at http://clinicaltrials.gov, registration number NCT02067845 .